A hadith evaluation on the identity, design, location and space planning of modern mosques in Malaysia - Nangkula, Utaberta; Othman, Hafsah; Mohd Yunus, Mohd.Yazid; Ismail, Nor Atiah; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
This paper attempts to re-organize and analyses the Prophetic Hadith in giving an alternative approach for the designs of modern mosques in Malaysia. The research has been done by collecting traditions in the collections of al-Bukhari and Muslim which are then elucidated and formulated as a reference-framework for handling various issues and confusion in the making of designs of modern mosques in Malaysia. This research consists of documentations and analysis of the collections of the Prophetic traditions concerned in illuminating various issues and problems on the designs of mosques in Malaysia and the world. Hopefully, through this research in this paper we can understand the utilization of the Propetic Tradition as one of the main alternative approaches and reference frameworks in bringing out modern mosque designs in Malaysia for the present and the future.